Evaluation of some plant extracts in control damping-off and mildew diseases of cucumber - Tohamy, M. R. A.; Aly, A. z.; Abd-El-Moity, T. H.; Atia, M. M. UNAUTHORIZED>; Abd-El-Moneim, Maisa L. (2002)
Plant extracts of neem, camphor leaves and garlic bulb reduced linear growth of cucumber soil-borne pathogens. The most effective concentration in this regard was 5%. Plant preparations tested, either in the form of suspension or as a powder, significantly reduced disease incidence. On the other hand, neem and garlic plant extracts drastica11y reduced incidence of powdery and downy mildews disease. It is also clear that, garlic extract was more effective than neem extract. Four weeks cucumber plants responded positively to weekly sprays with neem and garlic extracts at all concentrations tested These treatments reduced either powdery or downy mildew diseases and increased number as well as weight of fruits/plant compared with check treatment.
Includes references.
Summary in Arabic.
1
Keywords: Cucumbers -- Diseases and pests; Plant extracts; Powdery mildew diseases; Soilborne plant diseases